A Japanese case of mitochondrial 3‐hydroxy‐3‐methylglutaryl‐CoA synthase deficiency who presented with severe metabolic acidosis and fatty liver without hypoglycemia. Issue 1 (3rd June 2019) - Lee, Tomoko; Takami, Yuichi; Yamada, Kenji; Kobayashi, Hironori; Hasegawa, Yuki; Sasai, Hideo; Otsuka, Hiroki; Takeshima, Yasuhiro; Fukao, Toshiyuki
Abstract: Mitochondrial 3‐hydroxy‐3‐methylglutaryl‐CoA synthase deficiency (mHS deficiency) is a rare autosomal recessive inborn error of ketogenesis caused by a mutation in the HMGCS2 gene, which is characterized by non‐(hypo)‐ketotic hypoglycemia, lethargy, and hepatomegaly during acute infection and/or prolonged fasting. Clinical presentations are similar to fatty acid oxidation defects; however, diagnosis of mHS deficiency is difficult because of poor biochemical markers. We report the case of a 12‐month‐old Japanese boy with mHS deficiency who presented with a coma, and hepatomegaly, but no hypoglycemia after a febrile episode and poor oral intake. Metabolic acidosis and severe fatty liver were observed. Serum acylcarnitine analysis revealed a slightly decreased free carnitine (C0) level and an increased acetylcarnitine (C2) level. Urinary organic acid analysis revealed hypoketotic dicarboxylic aciduria, and increased excretions of glutarate, and, retrospectively, 4‐hydroxy‐6‐methyl‐2‐pyrone. Although the patient did not present with hypoglycemia, the severe fatty liver and elevated free fatty acids to total ketone bodies ratio strongly suggested an inborn error of ketogenesis. In the analysis of the HMGCS2 gene, compound heterozygous mutations of c.130_131ins C (L44PfsX29) and c.1156_1157insC (L386PfsX73) were identified, which led to the diagnosis of mHS deficiency. He had recovered without any complication by the therapy, including intravenous glucose infusion. Unlike the previously reported cases of mHS deficiency, our case did not present with hypoglycemia and the fatty liver lasted over several months. mHS deficiency should be taken into consideration when a patient has severe metabolic acidosis and fatty liver with no or subtle ketosis, even without hypoglycemia.